Evaluation of different types of soil subgrade using glass powder for Low-Volume Roads (LVRs). (2022) - Harinder, D.; Chandu, B.; Aditya, M.
Abstract: Flexible pavement structure consists of number of layer to pose the various function required to maintain a durable pavement over long durability. In order to provide the durable pavement structure over the week subgrade, it consumes larger thickness of natural materials. To avoid such problem and stabilize the available week sub-grade soil. The use of industrial waste in pavement structure gains attention to reduce the natural resource in pavement structure. Last few decades, the utilization of industrial material waste had become immensely in the growing world of construction. In pavement to strengthen the weak sub-grade soil, these products are fulfil the requirements and also showed the outmost performance in pavement structure. In view of the above, this study was conducted on weak sub-grade soil with the different other practically with the additives of glass powder. The glass powder were added in various percentages to the soil mass of sub grade. The experimental study were carried-out The Standard Proctor Test (SPT), Shear Strength (SS), California Bearing Ratio (CBR) Test to determine the optimum (%) of glass powder with the different type of sub-grade soil. This study concluded that, the use of glass is pozzolanic material improved the strength of weak sub-grade soil. The optimum glass powder is found as 15% for the both the types of soil sub-grade.